2016
DOI: 10.5210/fm.v21i11.6996
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting for peace? Twitter and the Ardoyne parade dispute in Belfast, July 2014

Abstract: This paper explores how social media can facilitate peace building by focusing on how citizens used Twitter during a contentious march in the Ardoyne district of North Belfast in July 2014. Fears of a repeat of sectarian clashes seen a year earlier were not realized, and the study was designed to empirically investigate whether critics and supporters of the Orange Order used the microblogging site to help reduce the sectarian tensions that surrounded the contentious parade. In particular, it focused on how use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Although our focus was on its broadcasting and gatekeeping dynamics, it was still important to identify the most active tweeters in #PorteOuverte. Similar to previous research into crisis hashtags (Bruns et al, 2012;Lotan et al, 2011;Reilly, 2016), there was a long-tail distribution of user activity within #PorteOuverte. A total of 208,015 tweeters were identified in the corpus, the majority of whom (149,671 or 71.2%) only posted once during the night of the terror attacks.…”
Section: Top 50 #Porteouverte Tweeterssupporting
confidence: 82%
See 2 more Smart Citations
“…Although our focus was on its broadcasting and gatekeeping dynamics, it was still important to identify the most active tweeters in #PorteOuverte. Similar to previous research into crisis hashtags (Bruns et al, 2012;Lotan et al, 2011;Reilly, 2016), there was a long-tail distribution of user activity within #PorteOuverte. A total of 208,015 tweeters were identified in the corpus, the majority of whom (149,671 or 71.2%) only posted once during the night of the terror attacks.…”
Section: Top 50 #Porteouverte Tweeterssupporting
confidence: 82%
“…Moreover, the "democratizing" potential of these hashtags should not be overstated. While citizens do have greater opportunities to co-curate information flows during hybrid media events, content posted by bloggers and professional journalists continues to be the most widely shared on Twitter (Chadwick, 2013;Lotan et al, 2011;Reilly, 2016).…”
Section: #Porteouverte As a Ritualized Connective Action During Terromentioning
confidence: 99%
See 1 more Smart Citation
“…Today, authorities have adapted to social media environments too and share their perspective from protest events (Neumayer et al, 2016). Yet, while authorities antagonize the protesters and the protests themselves by sharing visual content focused on violence initiated by activists (Neumayer & Rossi, 2018), citizens try to create a counter-narrative to the dominant portrayal of protest events or correct rumors and disinformation by mainstream media and police via the sharing of visual content witnessing violence as injustice by police (Hermida & Hernández-Santaolalla, 2018; Reilly, 2016).…”
Section: Measuring the Propagation Of Image Tweets From Protestmentioning
confidence: 99%
“…Dominant Twitter accounts often belong to traditional media and politicians, so one cannot assume that digital platforms represent a liberal independent media sphere (Golovchenko et al, 2018). Some preliminary work (though not focusing specifically on war and peace framing indicators), explored how social media can facilitate peace building by examining how citizens used Twitter during a contentious 2014 parade dispute in Belfast Findings showed that while the platform empowered citizens to correct rumors and disinformation, it appears to have failed in fostering cross-community consensus on how to resolve the dispute and promote peace (Reilly, 2016).…”
Section: Media Framing Of Conflictsmentioning
confidence: 99%